Improving Students’ English Speaking Skill Through Guided Conversation At SMK Industri Nasional 1 Setu Bekasi - Masriyah, Masriyah; Siahaan, Leroy Holman; Sari, Tiara Dian (CV. ITTC INDONESIA, 2024)
This study aims to determine how far students' ability to speak English has improved, as well as to experiment with guided conversation techniques in English learning. This study applies the classroom action research method. The subjects of the study are 26 students from class X (TKJ) at SMK Industri Nasional 1 Setu Bekasi for the 2023 school year. The results of this study show that using guided conversation to help students in learning English, especially speaking ability has proven to be successful. This is supported by data from this study. First, the results of the interviews showed that students were more motivated and interested in learning English. Second, the meeting included three tests: Pre-test, post-test of the first cycle, and post-test of the second cycle. After using the guided conversation approach, the percentage of students who passed the KKM increased by 50%: 38.64 for post-test I and 88.64 for post-test II. 23 out of 26 students passed the KKM, showing that classroom action research proved successful.